Positivity Expansion to Signed Solution for Doubly Nonlinear Parabolic Equations - Sarkar, Md Abu Hanif (Jagannath University Journal of Science, 2024)
We investigate doubly nonlinear parabolic equation with sign changing solutions. We established the expansion of positivity to the sign changing solution within a parabolic domain which is the key elements to achieve the regularity results. Jagannath University Journal of Science, Volume 10, Number I, Jun. 2023, pp. 64−74